Significance of tenascin serum level as tumor marker in primary colorectal carcinoma - Riedl, Stefan; Bodenmüller, Heinz; Hinz, Ulf; Holle, Rolf; Möller, Peter; Schlag, Peter; Herfarth, Christian; Faissner, Andreas (International journal of cancer, 1995)
Tenascin serum levels were evaluated in 118 patients with primary colorectal carcinoma and in a control group of 51 healthy persons in a double-sided sandwich ELISA. The data were correlated with post-operative TNM-staging. Patients with colorectal carcinomas had significantly higher serum levels of tenascin than the control group. At the 95% level of specificity, sensitivity was 25%. Tumor grading obviously had no influence on the level of tenascin in serum. With increasing pT-category, tenascin levels increased as well. In patients with distant metastatic disease, serum tenascin levels were significantly higher than in patients without distant metastases. These data suggest that, in colorectal carcinoma, the preoperative level of serum tenascin reflects the total tumor burden and correlates with metastatic disease. Our observation warrants a prospective study of the relevance of tenascin serum levels with regard to prognosis and as an indicator of relapse. © 1995 Wiley-Liss, Inc.